A review of geochemical–mechanical impacts in geological carbon storage reservoirs. Issue 3 (3rd May 2019) - Akono, Ange‐Therese; Druhan, Jennifer L.; Dávila, Gabriela; Tsotsis, Theodore; Jessen, Kristian; Fuchs, Samantha; Crandall, Dustin; Shi, Zhuofan; Dalton, Laura; Tkach, Mary K.; Goodman, Angela L.; Frailey, Scott; et al.
Abstract: Geological carbon storage (GCS) refers to the technology of capturing man‐made carbon dioxide (CO2 ) emissions, typically from stationary power sources, and storing such emissions in deep underground reservoirs. GCS is an approach being explored globally as a defense mechanism against climate change projections, although it is not without its critics. An important focus has been recently placed on understanding the coupling between rock–fluid geochemical alterations and mechanical changes for CO2 storage schemes in saline aquifers. This article presents a review of the current state of knowledge regarding CO2 ‐induced geochemical reactions in subsurface reservoirs, and their potential impact on mechanical properties and microseismic events at CO2 storage sites. This review focuses, in particular, on the current state of the art in fluid–rock interactions within the GCS context. Key issues to be addressed include geochemical reactions and the alteration of transport and mechanical properties. Specific review topics include the swelling of clays, the prediction of dissolution and precipitation reaction rates, CO2 ‐induced changes in porosity and permeability, constitutive models of chemo–mechanical interactions in rock, and correlations between geochemical reactions and induced seismicity. The open questions in the field are emphasized, and new research needs are highlighted. © 2019 Society of Chemical Industry and John Wiley & Sons, Ltd.